Putting Pleasure First: Localizing Japanese Video Games - O’Hagan, Minako (TTR, 2009)
Since their humble beginnings, video games have undergone huge technological advances, becoming a significant global industry today and highlighting the role played by translation and localization. Despite the continuing localization activities undertaken in the industry, translation studies (TS) have not paid much attention to video games as a research domain. Drawing on the author’s previous work on the Japanese Role Playing Game (RPG) Final Fantasy titles, this paper attempts to demonstrate the ample research scope that this domain presents for TS scholars. In particular, it discusses the unique localization model used by Final Fantasy’s Japanese publisher, illustrating how the games’ new digital platform allows the (re)creation of a new gameplaying pleasure directly through the localization process itself. In this model, the original game merely sets off a chain of improvements through localization. In turn, understanding the different pleasures drawn from different localized versions of games will contribute useful insights into emerging games research.